The economics of safety: A case study of the UK offshore helicopter industry - Mitchell, S. (Cranfield University, 2006)
The International Civil Aviation Organisation maintains that future viability of air transportation may well be predicated on perception of safety rather than any more tangible measures. In order to keep safety risks at an acceptable level it advocates a change of fundamental approach to the system of safety management, one that is more proactive. This study examines the causes of such a requirement for change, and the scope for improving the efficiency of what Calabresi refers to as the second principal goal of accident law, namely accident cost reduction. First, testing the validity of the traditional approach to safety analysis and management, as stated in regulatory guidelines. Secondly, examining the possibility that the efficiency of safety cost-benefit analysis can be practicably improved. A subsequent aim is to find an empirically based proxy measure for the acceptability of risk by examining the outcomes to potential safety related risk scenarios. Such a measure, if validated, may convert many existing intangible assessments concerning safety management into more transparent and reliable judgements. The offshore helicopter industry has many unique characteristics, some of which derive from the fact that the customers, the oil & gas companies, are more powerful than the operators. Others relate to the absence of any intermodal competition, and passengers who are specially trained to be properly aware of their safety. As choice is severely limited, this population is also likely to reflect a much broader range of risk preference. A carefully structured questionnaire was presented to a sample of these passengers, and the responses analysed in depth. The conclusions of this study are that choice is driven by the perceptions of safety, and that market stability is only maintained with the pre-condition that safety is deemed acceptable. Further, the failure of this pre-condition will follow a predictable pattern, based on a normal distribution for the population. The recommendation of this study is that such reactions to perceptions of safety risk are given due consideration alongside traditional costbenefit analysis, and in so doing it is likely that more secondary and tertiary accident cost factors will be more fully addressed. This will improve the overall efficiency of accident costs reduction, and make a significant contribution to the aim of proactive safety management.